Effects of 18 Months of Growth Hormone Replacement Therapy on Bone Mineral Density in Patients with Adult Growth Hormone Deficiency: A Retrospective Study. (31st March 2023) - Shen, Ya-Yin; Ma, Jia-Ni; Ren, Zi-Yu; Liu, Jie; Zhou, Xin-Yi; Xie, Xue-Rui; Ren, Wei
Abstract : Objective . The effect of physiological dose growth hormone (GH) replacement therapy on bone mineral density (BMD) in adults with growth hormone deficiency (GHD) is not well defined. We aimed to investigate the effects of 18 months of treatment with recombinant human growth hormone (rhGH) at physiological doses on BMD, body composition (BC), and quality of life (QoL). Methods . Sixty-eight patients diagnosed with adult growth hormone deficiency (AGHD) in our hospital were included in this retrospective study. All patients received individualized rhGH replacement to maintain normal serum insulin-like growth factor-1 (IGF-1) levels. BMD and BC measurements were performed by dual energy X-ray absorptiometry (DXA). Excluding those with incomplete follow-up data, we analyzed BMD in 68 patients, as well as BC and QoL in 36 of them. Results . Compared with the baseline, lumbar spine BMD decreased by 0.008 g/cm 2 (P = 0.006 ) and increased by 0.011 g/cm 2 (P = 0.045 ) at month 18, and total hip BMD decreased by 0.005 g/cm 2 (P = 0.008 ) and did not change significantly from the baseline at month 18. The changes in BMD did not differ by sex, and the increase in BMD was more pronounced in patients with low Z -scores at the baseline (lumbar spine: P = 0.005 and total hip: P = 0.018 ). The percentage change from the baseline in BMD was greater for the lumbar spine than for the total hip (P = 0.003 ). Lean body mass (LBM) increased significantly (P = 0.012 ), total body fat ratio (TBF%) decreased significantly (P = 0.011 ), visceral adipose tissue (VAT) decreased significantly (P = 0.016 ), and QoL improved significantly (P < 0.001 ). Conclusions . Within 18 months of treatment, bone resorption manifested first, BMD decreased to a nadir at month 6, and then it increased. The increase in BMD was greater in the lumbar spine than in the hip, and the increase was more pronounced in patients with low BMD. Eighteen months of rhGH replacement therapy significantly improved lumbar spine BMD and improved BC and QoL.